FORAMATION OF ORGANS AND ORGAN SYSTEMS IN NON-INTENSTIONAL TURBELLARIA - EHTESHAM RABBANI (International Journal of Multidisciplinary Research and Studies, 2020)
The Platyhelminthes historically contain organisms grouped in three major clades, Acoelomorpha, Catenulida, and Rhabditophora, which include the Neodermata (Figure 1.1). The Neodermata (Ehlers, 1985) comprises the group of the parasitic Platyhelminthes: Monogenea (Monopisthocotylea and Polyopisthocotylea), Trematoda (Aspidogastrea and Digenea), and Cestoda (Amphilinidea, Gyrocotylidea and Eucestoda) (Littelwood et al., 1999). They are characterized by the presence of a neodermis (hence the name of this parasitic clade), which is a specialized epidermis formed by a peripheral syncytium with cytoplasmic elongations. Monogenea are normally ectoparasitic on aquatic vertebrates, such as fishes, whereas trematodes and cestodes are exclusively endoparasitic, generally in vertebrates. The Platyhelminthes, both parasitic and free-living taxa, share a set of characters: they are nonsegmentedacolomates without an anus, which lack respiratory and circulatory systems but possess an excretory system. In addition, all are hermaphroditic and asexual (mainly paratomy) and sexual reproduction are present. The classical characteristics defining the phylum Platyhelminthes are: bilateral symmetry, multiciliated epidermis, absence of an accessory centriolus at the ciliary roots, more